Production of Cassava Starch-based Biofilm Using Lignin and Nanocellulose from Durian Husk as Additives - Loiloes, Kanoksak; Enmak, Prayoon; Leabwan, Napatsorn; Nitiyon, Sukanya; Plaisen, Siwat (Thai Agricultural Research Journal, 2025)
Biofilm made from cassava starch is not durable for packing usage due to its easy breaking and short lifespan. A large amount of durian shells was useless and unutilized by industry; therefore, they were chosen to produce additives for biofilm production. This research aims to enhance the durability of cassava starch-based biofilm by incorporating lignin and nanocellulose extracted from durian husk in biofilm. The result indicated that the lignin and nanocellulose extracted from durian husk had a lignin content of 39.5% and nanocellulose of 10% by dry basis. Cassava starch-based biofilms were prepared with varying concentrations of durian husk lignin and nanocellulose, along with 30% glycerol by weight. The biofilm containing 3% lignin exhibited the best physical and chemical properties, including a tensile strength of 142.51±5.21 kgf/cm², film elongation of 10.81±0.53%, moisture content of 7.97±0.18%, and water solubility of 4.88±0.65%. The oxygen permeation rate is 109.1±15.48 cm³/m²/day, similar to the biofilm without additives (109.5±34.71 cm³/m²/day), a thickness of 0.185±0.00 mm and a color change (∆E) of 41.89±0.85. Cassava starch biofilms with 3% lignin from durian husk and 30% glycerol were more durable and can be used for dry food packaging because of their better physical properties.